Cross-border cooperation in the Neisse-Nisa-Nysa Euroregion; as an example - Hajduga, Piotr (Współpraca transgraniczna na przykładzie Euroregionu Neisse-Nisa-Nysa, 2017)
The article explores the issues related to cross-border cooperation in the Neisse-Nisa-Nysa Euroregion as an example. It also emphasises the need of cooperation between Poland, the Czech Republic and Germany in the area of economy, culture and tourism. Using an example of the Neisse-Nisa- Nysa Euroregion, the benefits from closer cooperation in neighbouring border regions are discussed.
Biblioteka Regionalisty, 2017, Nr 17, s. 31-42
Keywords: cross-border cooperation; euroregion; economic borderland; współpraca transgraniczna; pogranicze gospodarcze